Analysis of egg quality and growth-related factors during embryogenic development of olive flounder (Paralichthys olivaceus) fed different broodstock diets - Ji-Sung Moon; Minji Seong; Si-Chan Kim; Josel Cadangin; Ji-Hye Lee; Eun-Seo Lee; Bong-Seung Seo; Haham Kim; Su-Jin Park; Jukyoung Kim; Jinho Lee; Seunghyung Lee; et al. (Fisheries and Aquatic Sciences)
Egg quality serves as an early indicator of successful hatching and larval quality, both important for continuous larval culture production. The current study aimed to demonstrate the comparative effect of a formulated extruded pellet (EP) against a raw fish-based moist pellet (MP) as broodstock diet of olive flounder (Paralichthys olivaceus) on the egg quality and level of growth-related factors during the embryonic development of fertilized eggs. The egg quality parameters such as spawned eggs volume, fertilization rate, egg diameter, oil globule diameter, oil globule volume, hatching rate, malformation rate, and survival activity index (SAI) were compared after feeding either EP or MP to broodstocks for 2 months. Besides, the study assessed the time to reach embryonic stages and the concentration of growth-related factors (growth hormone, insulin-like growth factor, and lipovitellin) at various developmental stages. The results showed that spawned eggs volume, fertilization rate, oil globule volume, and SAI were higher in the EP group compared to the MP group. In contrast, higher egg diameter, oil globule diameter, hatching rate, and lower malformation rate were observed in the MP group compared to the EP group. Nevertheless, no significant difference was observed in most parameters (p > 0.05). The proximate composition of fertilized eggs revealed significantly higher protein (including amino acids) and lipid contents in the MP group than in the EP group (p < 0.05). In contrast, the fatty acids EPA and DHA content was significantly higher in the EP group than in the MP group (p < 0.05). Comparison of the time to complete embryogenesis until hatching into larvae of fertilized eggs showed that there was a difference between diets with EP group faster than MP. The concentration of growth-related factors in various developmental stages was affected by experimental diets. The former two were higher in the EP group, while the latter was higher in the MP group. The findings of this study demonstrate the positive effects and suitability of an EP diet as a broodstock diet for olive flounder seed production. However, maintaining the consistency and quality of the diet’s constituents is likely crucial to sustaining these positive effects.